Open Wide: Looking into the Safety Culture of Dental School Clinics. Issue 5 (1st May 2014) - Ramoni, Rachel; Walji, Muhammad F.; Tavares, Anamaria; White, Joel; Tokede, Oluwabunmi; Vaderhobli, Ram; Kalenderian, Elsbeth
Abstract : Although dentists perform highly technical procedures in complex environments, patient safety has not received the same focus in dentistry as in medicine. Cultivating a robust patient safety culture is foundational to minimizing patient harm, but little is known about how dental teams view patient safety or the patient safety culture within their practice. As a step toward rectifying that omission, the goals of this study were to benchmark the patient safety culture in three U.S. dental schools, identifying areas for improvement. The extensively validated Medical Office Survey on Patient Safety Culture (MOSOPS), developed by the Agency for Healthcare Research and Quality, was administered to dental faculty, dental hygienists, dental students, and staff at the three schools. Forty‐seven percent of the 328 invited individuals completed the survey. The "Teamwork" category received the highest marks and "Patient Care Tracking and Follow‐Up" and "Leadership Support for Patient Safety" the lowest. Only 48 percent of the respondents rated systems and processes in place to prevent/catch patient problems as good/excellent. All patient safety dimensions received lower marks than in medical practices. These findings and the inherent risk associated with dental procedures lead to the conclusion that dentistry in general, and academic dental clinics in particular, stands to benefit from an increased focus on patient safety. This first published use of the MOSOPS in a dental clinic setting highlights both clinical and educational priorities for improving the safety of care in dental school clinics.